Information System for Monitoring Follow-up on Audit Results as an Effort to Digitize the Audit Process at the National Civil Service Agency - Ramadhan, Hary Noval (SAN Scientific, 2025)
The follow-up process of examination results at the National Civil Service Agency (BKN) has so far been conducted manually using spreadsheets and physical documents, which has the potential to cause delays in reporting, data duplication, and low monitoring efficiency. This research aims to design and build a monitoring information system for follow-up on examination results as a form of digitalization of the audit process within the BKN. This system is developed using web-based technology, with Laravel as the backend framework, PHP as the main programming language, and MySQL as the database. The development process uses the Waterfall method which includes stages of analysis, system design using UML, implementation, and testing. To ensure the functionality of the system, black box testing is conducted which shows that all main features operate according to user requirements. In addition, the system evaluation was conducted through a user satisfaction questionnaire among several relevant employees at BKN, and achieved a satisfaction level of 87%, indicating a positive acceptance of the developed system. This system enables the recording, monitoring, and reporting of follow-up actions from inspections to be done in a structured, real-time, and well-documented manner, while also supporting increased transparency and accountability within governmental agencies.